PENGARUH MOTIF URBAN FARMING TERHADAP PERILAKU PENGGUNA MEDIA SOCIAL SEBAGAI CYBER EXTENSION - Harun, Faathiyah (Universitas Galuh, 2023)
Urban farming is a self-sustainable solution to meet consumption needs by utilizing small plots of land in residential areas. The practice of urban farming has gained recognition with the advancement of information technology, including the utilization of social media. Social media serves as a cyber extension, enabling the exchange of agricultural information through the digital world. Cyber extension is a form of tele-education that facilitates urban farming practitioners in accessing information related to urban farming techniques via social media. This research aims to analyze the influence of urban farming motives on the behavior of urban farming practitioners in using media. The study was conducted in the city of Makassar, where questionnaires were administered to 50 respondents based on predetermined criteria. Regression analysis was employed to analyze the data and address the research objectives. The results indicate that urban farming motives have a significant relationship and influence on the behavior of online media usage in seeking information related to urban farming. The urban farming motive affects the choice of social media platforms used by respondents to gather information about urban farming. Additionally, the motive also influences the attitudes and knowledge of respondents, assisting them in determining their behavior after receiving the information.